Mediating role of social capital in the association between socioeconomic status and childcare practices in rural Malawi: a cross-sectional study - Akira Shibanuma; Masamine Jimba; Junko Kiriya; Suhyoon Choi (BMJ Open)
Objectives Childcare practices determine the child nutritional outcomes, but resources for good practices are unequally distributed across socioeconomic status (SES). This study first examined the associations between social capital and childcare practices separately across SES groups. It then investigated the mediation effect of social capital between SES and childcare practices.Design This cross-sectional study used the Short Version of the Adapted Social Capital Assessment Tool to measure structural social capital (group membership, social support and citizenship activities) and cognitive social capital of mothers. Data were analysed using multilevel logistic regressions with random intercepts and mediation modellings.Setting Rural Lilongwe, Malawi.Participants A total of 320 mothers with a child aged between 12 months and 23 months.Primary outcome measures Childcare practice outcomes included were minimum dietary diversity, handwashing and complete vaccination.Results Among structural social capital dimensions, social support was found to be positively associated with minimum dietary diversity (adjusted OR (AOR)=1.44, 95% CI 1.22 to 1.71; p<0.001) and handwashing for all mothers (AOR=1.42, 95% CI 1.23 to 1.64; p<0.001). In the subgroup analysis, the higher SES group had higher odds of meeting the minimum dietary diversity (AOR=1.63, 95% CI 1.18 to 2.26; p=0.01) and handwashing with increased social support (AOR=1.53, 95% CI 1.13 to 2.08; p=0.01) than the lower SES. The mediation effect of social support accounted for 27.3% of the total effect between SES and minimum dietary diversity. Cognitive social capital was negatively associated with vaccination for the lower SES group (AOR=0.07, 95% CI 0.01 to 0.68; p=0.03).Conclusions To improve feeding and handwashing practices and to reduce health inequalities in rural Malawi, governments and organisations should consider promoting the value of social support and health. Future research is needed to explain the negative association between cognitive social capital and vaccination among the lower SES group.